Metabolic and molecular insights into an essential role of nicotinamide phosphoribosyltransferase - Zhang, Li Q (Cell Death Dis, 2017)
Nicotinamide phosphoribosyltransferase (NAMPT) is a pleiotropic protein implicated in the pathogenesis of acute respiratory distress syndrome, aging, cancer, coronary heart diseases, diabetes, nonalcoholic fatty liver disease, obesity, rheumatoid arthritis, and sepsis. However, the underlying molecular mechanisms of NAMPT in these physiological and pathological processes are not fully understood. Here, we provide experimental evidence that a Nampt gene homozygous knockout (Nampt(−/−)) resulted in lethality at an early stage of mouse embryonic development and death within 5–10 days in adult mice accompanied by a 25.24±2.22% body weight loss, after the tamoxifen induction of Nampt(F/F) × Cre mice. These results substantiate that Nampt is an essential gene for life. In Nampt(−/−) mice versus Nampt(+/+) mice, biochemical assays indicated that liver and intestinal tissue NAD levels were decreased significantly; histological examination showed that mouse intestinal villi were atrophic and disrupted, and visceral fat was depleted; mass spectrometry detected unusual higher serum polyunsaturated fatty acid containing triglycerides. RNA-seq analyses of both mouse and human pediatric liver transcriptomes have convergently revealed that NAMPT is involved in key basic cellular functions such as transcription, translation, cell signaling, and fundamental metabolism. Notably, the expression of all eight enzymes in the tricarboxylic acid cycle were decreased significantly in the Nampt(−/−) mice. These findings prompt us to posit that adult Nampt(−/−) mouse lethality is a result of a short supply of ATP from compromised intestinal absorption of nutrients from digested food, which leads to the exhaustion of body fat stores.